2018
DOI: 10.1111/are.13710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polysaccharides extracts of algae Ulva rigida on growth, antioxidant, immune response and resistance of shrimp, Litopenaeus vannamei against Photobacterium damselae

Abstract: This study was carried out to investigate the effect of water‐soluble polysaccharides extract of algae Ulva rigida (WPU) as dietary supplement on growth performance, antioxidant enzyme activity, lysozyme and phenoloxidase activity, and resistance of shrimp (Litopenaeus vannamei) subjected to bacterial infection with Photobacterium damselae. Three replicate groups of shrimp (1.0 g) were fed four diets containing four levels, 0 or control, 0.5, 1 and 1.5 g/kg of WPU for 8 weeks over the growth trial. Thereafter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…This is well established that increased reactive oxygen species (ROS) levels will lead to oxidative stress, which may negatively affect the sh and crustaceans' health and cause structural damage in tissue cells (Akbary and Aminikhoei 2018;Tavabe et al 2020). Antioxidant defense system includes some pivotal enzymes such as superoxide dismutase (SOD) and catalase (CAT) that tend to prevent ROS formation (Yonar et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is well established that increased reactive oxygen species (ROS) levels will lead to oxidative stress, which may negatively affect the sh and crustaceans' health and cause structural damage in tissue cells (Akbary and Aminikhoei 2018;Tavabe et al 2020). Antioxidant defense system includes some pivotal enzymes such as superoxide dismutase (SOD) and catalase (CAT) that tend to prevent ROS formation (Yonar et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of this study, the inclusion of MPE in the diet improved the antioxidant activity of the L. vannamei shrimp as compared with shrimps on the control diet. Akbary and Aminikhoei (2018a) reported that the inclusion of 1.5 g kg − 1 of U. rigida algae extract in the diet of shrimps signi cantly increased the activity of SOD and reduced glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Roosta et al (2014) observed an increase in the activity of mucus alkaline phosphatase in Rutilus rutilus caspicus following dietary supplementation with high levels of AA. This is well established that increased reactive oxygen species (ROS) levels will lead to oxidative stress, which may negatively affect the sh and crustaceans' health and cause structural damage in tissue cells (Akbary and Aminikhoei 2018;Tavabe et al 2020). Antioxidant defense system includes some pivotal enzymes such as superoxide dismutase (SOD) and catalase (CAT) that tend to prevent ROS formation (Yonar et al 2014).…”
Section: Discussionmentioning
confidence: 99%